2017
DOI: 10.1159/000475834
|View full text |Cite
|
Sign up to set email alerts
|

NICU Human Milk Dose and 20-Month Neurodevelopmental Outcome in Very Low Birth Weight Infants

Abstract: Background: The association between human milk (HM) feeding in the NICU and neurodevelopmental (ND) outcome in very low birth weight (VLBW) infants is unclear. Limitations of previous studies include a lack of exact estimates of HM dose and of generalizability to minority populations. Objective: To determine the impact on ND outcome of an exact dose of HM received in the NICU in a diverse, contemporary cohort of VLBW infants. Methods: We included 430 VLBW infants born in the period 2008-2012 for whom the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 24 publications
1
53
2
2
Order By: Relevance
“…The benefits or effect of human milk or DHM on morbidity, specifically necrotising enterocolitis, late onset sepsis, retinopathy of prematurity, bronchopulmonary dysplasia, early achievement of full feeding, encourage successful catch-up growth and neurodevelopment in preterm infants have been well known [ 9 11 , 36 , 37 ]. Meanwhile, some studies found that these protective effects showed a time- and dose-dependent relationship [ 38 ]. Therefore, it was still necessary to observe and verify whether there was significant effect on these premature babies when they were provided with such a short time and so little HDM.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits or effect of human milk or DHM on morbidity, specifically necrotising enterocolitis, late onset sepsis, retinopathy of prematurity, bronchopulmonary dysplasia, early achievement of full feeding, encourage successful catch-up growth and neurodevelopment in preterm infants have been well known [ 9 11 , 36 , 37 ]. Meanwhile, some studies found that these protective effects showed a time- and dose-dependent relationship [ 38 ]. Therefore, it was still necessary to observe and verify whether there was significant effect on these premature babies when they were provided with such a short time and so little HDM.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding with human breast milk rather than formula is the simplest family-centred, valued and effective immunoprotective strategy [49, 50]. Donor breast milk may be beneficial for infants whose mothers cannot provide expressed breast milk, but the cost-effectiveness of this policy remains to be established in some contexts and settings.…”
Section: Resultsmentioning
confidence: 99%
“…Of all the parent-delivered interventions, the two most thoroughly studied and powerful interventions that can only be provided by parents are breast milk/breast feeding (Belfort et al, 2016) and skin-to-skin contact, which is also known as the Kangaroo care position. Breast milk and breastfeeding are considered to provide the optimal nutrition for all infants, and to confer immune protection, more appropriate growth, and neurodevelopmental advantage for preterm infants (Patra et al, 2017). Skin-to-skin contact has a multitude of positive effects including supporting infant physiological stability, preventing pain, strongly promoting infant growth and neurobehavioral development, and improving breast feeding (quantity and duration) (Boundy et al, 2016;Holditch-Davis et al, 2014;Johnston et al, 2017;Karimi, Sadeghi, Maleki-Saghooni, & Khadivzadeh, 2019;Lumbanraja, 2016;Nyqvist et al, 2010;Sweeney, Rothstein, Visintainer, Rothstein, & Singh, 2017).…”
Section: Parent-delivered Interventionsmentioning
confidence: 99%